The effects of a multigrowth factor‐containing cream on recovery after laser treatment: a double‐blinded, randomized, split‐face controlled study. (16th September 2016) - Shin, Sungsik; Shin, Jung U; Lee, Youngin; Kwon, Tae Gwang; Lee, Ju Hee
Summary: Background: Patients who receive laser treatments may experience transient erythema, edema, and crusts for several days. Although a variety of growth factor‐containing creams for promoting recovery after laser treatment are available, evidence for their efficacy remains insufficient. Aims: We performed a randomized controlled split‐face study to assess the effects of a multigrowth factor (MGF)‐containing cream on patients recovering from laser treatment. Materials and Methods: Twenty patients underwent treatment using an ablative fractional laser and were randomized with respect to the side of the face treated with an MGF‐containing cream or control cream. We measured post‐treatment erythema and pigmentation using the erythema and melanin indices, respectively, and evaluated the total area of microcrusts with dermoscopy. Additionally, patient satisfaction levels and global improvement scores were assessed. Results: We found that the area of microcrusts was significantly smaller in the MGF‐treated regions. Global improvement scores for post‐treatment edema and wrinkles were also significantly higher for MGF cream‐treated sides than for the control sides. Conclusion: The MGF cream‐treated regions showed a more rapid recovery from crusts and edema. Thus, the use of an MGF‐containing cream after laser treatment can effectively reduce recovery time.